Effect of potassium permanganate on morphological, structural and electro-optical properties of graphene oxide thin films - Muhammad, Kashif; Erdawaty, Jaffar; Poonam, Bhadja; Low, Foo Wah; Siti Kudnie, Sahari; Shahid, Hussain; Loong, Foo Kai; Awais, Ahmad; Tahani Saad, AlGarni; Muhammad, Shafa; Humaira, Asghar; Saad A., Al-Tamrah (Elsevier B.V., 2021)
This work investigated the effect of Potassium Permanganate (KMnO4) on graphene oxide (GO) properties, especially on electrical properties. The GO thin films were deposited on a glass substrate using drop casting technique and were analysed by using various type of spectroscopy (e.g. Scanning Electron Microscopy (SEM), Ultra- Violet Visible (UV–VIS), Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD), optical band gap, Raman Spectroscopy).